#TITLE_ALTERNATIVE# - KHRISNA DEWANGGA (NIM : 13606021); Dosen Pembimbing: Dr. Djarot Widagdo; Dr.Eng Arif Sugian, WAHYU
In one of its flight, the left main landing gear of B737-400 broken at the axle just after it touched down. Failure analysis carried out by KNKT together with GMF AeroAsia showed the indication of fatigue failure started from a crack initiated at the edge of a flange hole. The crack initiation shows the sign of corrosion pit. To obtain a complete picture of the failure mechanism, the analysis needs to be supported by the understanding of load experience by the failed landing gear. The loads are then used in a stress analysis to obtain stress distribution in the landing gear. The result of stress distribution is usefull to show the critical sites in the landing gear which experience stress concentration. To assure the result of finite element analysis, the model is validated by applying simple load cases into the model from which the result can be compared to analytical calculation. Convergence study is also carried out to assure the quality of model meshing. Loading analyses show the load equivalent to dynamic load at touch down is the critical loading will be received by the landing gear. Stress analysis shows the stress concentration occurred in the landing gear including around the hole where the fatigue failure started.